The epistemic trust assessment: an experimental measure of epistemic trust - Schröder-Pfeifer, Paul; Georg, Anna; Talia, Alessandro; Volkert, Jana; Ditzen, Beate; Taubner, Svenja (Psychoanalytic psychology, 2022)
Epistemic Trust (ET) describes an individual’s trust in the relevance of interpersonally transmitted information. While this concept increasingly informs theories of communication and psychopathology, as well as psychoanalytic change theory, there currently exists no rigorous way of measuring ET. This study describes an experimental paradigm for assessing ET. We designed the ET assessment (ETA) procedure in which we first utilized the Trier Social Stress Test for Groups, which asks participants to engage in public speaking and mental arithmetic in front of two evaluators and other experimental participants. Next, the participants were individually administered a questionnaire, which asked questions about participants’ own behavior and overall performance during the interview. Participants were then given a standardized feedback about their behavior and performance, which included information about aspects in which the evaluators were “trustworthy informants” (e.g., participants’ objectively measured physiology) and “untrustworthy informants” (e.g., participants’ mental states), and they were then asked if they wanted to revise their previous answers. ET was operationalized as the extent to which participants were able to adequately modify their perspective on the basis of evaluators’ trustworthy feedback. We controlled for social desirability and personality disorder traits using the Short Scale for Social Desirability (KSE-G) and the short form of the Inventory of Personality Organization (IPO-16). The results confirmed our hypothesis. A majority of participants endorsed trustworthy feedback and rejected untrustworthy feedback. The ETA can be used as an internally validated measure of ET. Future studies validating the ETA in a clinical population are warranted. (PsycInfo Database Record (c) 2022 APA, all rights reserved)